A tool for incorporating interprofessional perspectives into dental students decision‐making: A 2‐year follow‐up on this learning outcome. Issue 5 (19th June 2022) - Craig, Trevor W.; Comnick, Carissa L.; Leary, Kecia S.; Hartshorn, Jennifer E.; Johnsen, David C.; Marchini, Leonardo
Abstract: Objectives: To analyze student performance when using a sustainable teaching tool developed to guide learning toward interprofessional perspectives. Methods: This study compiled data about D4 students' performance when using an interprofessional education (IPE) teaching tool reported previously in this journal, during their 5‐week Geriatric and Special Needs Program rotation in the academic years 2018–2019 and 2019–2020. Ninety‐two students were introduced to IPE concepts and teaching tools during their orientation. Students were then asked a question regarding the perspective of each healthcare team member and whether they would contact these healthcare team members for collaboration during the provision of oral care with regard to various patient cases. Students were scored on whether they answered the question about the perspective of each health care team member. The same two independent evaluators also noted whether the student thought each member of the health care team should be contacted. Results: A majority (90.2%–95.7%) of dental students applied their knowledge to questions regarding each health care team member's perspectives. The profession that dental students most often indicated they wished to contact for collaboration was primary care providers ( n = 70; 76.1%), followed by family caregivers ( n = 54; 58.7%), and pharmacists ( n = 46; 50.0%). The results of the interrater agreement between the two‐faculty scoring students were between 86.7% and 100%. Conclusions: The teaching tool is sustainable and succinct. Students considered the perspectives of each health care team member at a rate above 90%, and the interrater agreement was high among the faculty evaluators. Students considered contacting primary care providers, family caregivers, and pharmacists more often than the other health care team members. We see this model as one approach to begin the articulation of learning outcomes for IPP.